The weblog: a tool for literary translators. - Haddadian Moghaddam, Esmaeil (Perspectives: Studies in Translatology, 2013)
The application of weblogs to on-line translation workshops is a new research area in Translation Studies. In this article, the author extends the use of weblogs to literary translation in a new framework, and argues that the weblog has the potential to be a communication and documentation translation tool. The weblog helps the literary translator in the translation process and in the post-translation phase in a number of ways. It can act as a ‘mediator’ between the author of the work under translation, the translator, and the prospective readers. It also provides facilitated ‘collaborative possibilities’ for the translation itself, by creating a virtual world around the translation which is bigger than the translator's small, isolated space. The author also examines the ways the weblog may become an impediment to the translation or even to the literary translator, and offers some solutions in order to optimize its application to literary translation.